Bottom-up effects of Brassica genotypes on performance of diamondback moth, Plutella xylostella (Lepidoptera: Plutellidae). (January 2019) - Fathipour, Yaghoub; Kianpour, Roja; Bagheri, Abdoolnabi; Karimzadeh, Javad; Hosseininaveh, Vahid
Abstract: The adverse effects of excessive application of insecticides is causing a renewed interest to find resistant host plants to insect pest. Herein, we attempted to elucidate the bottom-up effects of five canola cultivars (Elite, SLM046, Star, NSA2, and RGS003 ), four cabbage cultivars (Glob-Master, Green-Cornet, Red-Rocky and Mikado) and one cauliflower cultivar (S-Mila) on the life table and biological parameters of diamondback moth, Plutella xylostella L., (Lepidoptera: Plutellidae). The age-stage, two-sex life table theory was used to unveil biological differences of P. xylostella on the Brassica genotypes. All experiments were carried out in a laboratory at 25 ± 1 °C, 65 ± 5% and a photoperiod of 16:8 (L: D) hours. The development time of P. xylostella varied from 13.0 days (on Elite) to 17.4 days (on Red-Rocky). The highest and lowest of net reproductive rate ( R 0 ) were recorded in NSA2 (27.0 offspring/individual) and Red-Rocky (4.7 offspring/individual), respectively. The intrinsic rate of increase ( r ) ranged from 0.072 day −1 on Glob-Master to 0.169 day −1 on Star. The mean generation time ( T ) value varied between 18.1 days on RGS003 to 22.5 days on Red-Rocky. According to the results inferred from biological and demographical parameters studies, Glob-Master and SLM046 were found as the resistant and susceptible cultivars, respectively. Revealing the resistance range of the studied Brassica cultivars and life history traits of P. xylostella on these cultivars provide insight into the eco-friendly control strategies of the pest through decreasing its damage rate and improving the condition for activity of natural enemies. Graphical abstract: Image 1 Highlights: Resistant Brassica cultivars can help in the development of multifaceted controls for P. xylostella .